2014
DOI: 10.15430/jcp.2014.19.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Chemoquiescence for Ideal Cancer Treatment and Prevention: Where Are We Now?

Abstract: Cellular quiescence is a state of reversible cell cycle arrest and is associated with a low metabolic state featured with decreased glycolysis, reduced translation rates, and activation of autophagy, fundamentally to provide nutrients for cell survival similar as seen in hybernation. As signal for quiescence, inactivating the target of rapamycin kinase and resulting reduced cell growth and biosynthesis are essential, but cellular quiescence is not always associated with reduced metabolism since it is also poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…[23][24][25][26][27][28] Rapamycin, for example, is a potent candidate to trigger autophagic activity in patients diagnosed for different types of cancer. 29,30 However, this compound enhances autophagy by blocking the MTOR (mechanistic target of rapamycin, [serine/threonine kinase]) kinase system, which in turn affects translation. Perturbation of general protein synthesis is certainly not a desired purpose in medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28] Rapamycin, for example, is a potent candidate to trigger autophagic activity in patients diagnosed for different types of cancer. 29,30 However, this compound enhances autophagy by blocking the MTOR (mechanistic target of rapamycin, [serine/threonine kinase]) kinase system, which in turn affects translation. Perturbation of general protein synthesis is certainly not a desired purpose in medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In all three cases our data revealed subpopulations of cells with slow OCR and ECAR in both control and treated cells. While further studies are necessary to reveal the functional role of these cells at the population and tissue level, it is possible that due to their dormant-like metabolic phenotype behavior these cells may play a role in drug response and cancer recurrence after treatment3132.…”
Section: Discussionmentioning
confidence: 99%
“…This is a state of reversible cell cycle arrest, associated with reduced translation rate, activation of autophagy, and a low metabolic rate as characterized by decreased glycolysis. 86 This is a burgeoning area of research and it has been suggested that the efficacy of CSC inhibitors and conventional therapies may be enhanced if used in combination with chemoquiescence-inducing agents such as chloroquine and its analogues.…”
Section: Induction Of Cellular Quiescencementioning
confidence: 99%